Learning Arabic for Beginners: Role-Based Small Group Discussion Cooperative Learning - Maulani, Hikmah; Faqih, Ahmad (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2021)
This study examines the innovation of learning strategies through Cooperative Learning by using Role-based Small Group Discussion. The purpose of this study is to reveal indicators that influence the success of learning through cooperative learning using Role-based Small Group Discussion. This study uses a qualitative method with the implementation of structured interviews and questionnaires, the use of this data collection method is carried out to reveal the views of the participants honestly. Respondents who became participants were students who came from public schools without any experience in learning Arabic. The results obtained were found indicators in the use of Role-based Small Group Discussion, namely attitudes, abilities, and usefulness of the method.